Self-Actualization and Anxiety in Early Adult Female Victims of Domestic Violence During Childhood - Fadhilah Umaira Alfahis; Naomi Soetikno (Philanthropy: Journal of Psychology)
Domestic violence (DV) is one of the forms of violence that affects not only adults but also children. Experiencing or witnessing DV in childhood can have long-term psychological impacts, such as the development of an anxious personality in adulthood. As individuals grow, they need to fulfill specific needs to achieve self-actualization, including safety needs. Individuals with high anxiety are most likely to have a threatened sense of security. Thus, the anxiety is predicted to be related to self-actualization. This research aims to investigate the relationship between self-actualization and anxiety in adult women who were victims of DV during childhood, with a total of 240 early adult women. The data analysis method is quantitative correlational. The findings revealed a correlation coefficient of -0.523 with a significance value of 0.000 (p < 0.05), indicating a negative correlation between self-actualization and anxiety in early adult women who experienced DV during childhood. Keywords: Anxiety, Self-Actualization, Domestic Violence